Gran's New Blue Shoes - Roderick Hunt (Bharat Oxford, 2003)
50 Books Level 1-6 pluss Brand new Edition Levels 1 - 3 Collection has been specially designed to introduce children aged four and above to the early concepts that will form the basis of their reading and writing skills. 4 to 6 are designed to help your child develop their reading skills and become a confident reader. Created by experts and based on current teaching practice, the books accurately reflect the curriculum's emphasis on phonic learning.
Keywords: IR - F -- IR - F